2016
DOI: 10.1111/joa.12536
|View full text |Cite
|
Sign up to set email alerts
|

How maturity influences annulus‐endplate integration in the ovine intervertebral disc: a micro‐ and ultra‐structural study

Abstract: The annulus-endplate anchorage system plays a vital role in structurally linking the compliant disc to its adjacent much more rigid vertebrae. Past literature has identified the endplate as a region of weakness, not just in the mature spine but also in the immature spine. The aim of this structural study was to investigate in detail the morphological changes associated with annulus-endplate integration through different stages of maturity. Ovine lumbar motion segments were collected from two immature age group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…This is important because it indicates that the analysed preparations were of a similar age. In animals, the GP undergoes mineralization as the aging process progresses (Casaroli et al, 2018; Rodrigues et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is important because it indicates that the analysed preparations were of a similar age. In animals, the GP undergoes mineralization as the aging process progresses (Casaroli et al, 2018; Rodrigues et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The integration at the inner AF, however, is more complex as the collagen fibers of the AF lamellae are continuous with those of the CEP (Figure 1). 49,56 Additionally, SEM analysis of ovine discs has shown that the collagen fibers of the AF branch, which strengthens the annulus–EP anchorage by increasing the interface area over which shear forces are distributed 57 . These fibers also intertwine and sometimes merge with the fibrils of the CEP.…”
Section: Healthy Cepmentioning
confidence: 99%
“… 49 , 56 Additionally, SEM analysis of ovine discs has shown that the collagen fibers of the AF branch, which strengthens the annulus–EP anchorage by increasing the interface area over which shear forces are distributed. 57 These fibers also intertwine and sometimes merge with the fibrils of the CEP. The strength of this connection is essential for the CEP ability to resist tensile loading.…”
Section: Healthy Cepmentioning
confidence: 99%
“…It is furthermore proposed that early fibre organisation informs the development of intracellular actin stress fibres within developing AF cells [86], which in turn may guide the production of aligned ECM and help redistribute mechanical loading as the IVD develops. Intriguingly, the orientation and integration of AF fibres into the BEPs, CEPs, and surrounding tissues appears to be driven by physical constraints caused by the emergence of the endplates and vertebral bodies [34,85,87], implying that physical matrix cues are central to AF development.…”
Section: Ivd Development and Maturationmentioning
confidence: 99%